The XXL survey. XLIX. Linking the members star formation histories to the cluster mass assembly in the z = 1.98 galaxy cluster XLSSC 122. Issue 2 (25th June 2022) - Trudeau, A; Willis, J P; Rennehan, D; Canning, R E A; Carnall, A C; Poggianti, B; Noordeh, E; Pierre, M
ABSTRACT: The most massive protoclusters virialize to become clusters at z ∼ 2, which is also a critical epoch for the evolution of their member galaxies. XLSSC 122 is a z  = 1.98 galaxy cluster with 37 spectroscopically confirmed members. We aim to characterize their star formation histories in the context of the cluster accretion history. We measure their photometry in 12 bands and create a PSF-matched catalogue of the cluster members. We employ bagpipes to fit star formation histories characterized by exponentially decreasing star-forming rates. Stellar masses, metal, and dust contents are treated as free parameters. The oldest stars in the red-sequence galaxies display a range of ages, from 0.5 Gyr to ∼3 Gyr. Characteristic times are between ∼0.1 and ∼0.3 Gyr, and the oldest members present the longest times. Using MultiDark Planck 2 dark matter simulations, we calculate the assembly of XLSSC 122-like haloes, weighted by the age posteriors of the oldest members. We found that 74 per cent of these haloes were <10 per cent assembled at the onset of star formation, declining to 67 per cent of haloes when such galaxies had formed half of their z = 1.98 stellar masses. When 90 per cent of their stellar masses were formed, 75 per cent of the haloes were <30 per cent assembled. The star formation histories of the red-sequence galaxies seem consistent with episodes of star formation with short characteristic times. Onset and cessation of star formation in the oldest galaxies are likely to precede XLSSC 122 virialization.